Thiopurine naivety at tacrolimus induction is a predictor of long‐term remission in patients with intractable ulcerative colitis who responded to tacrolimus. Issue 1 (1st October 2022) - Takatsu, Noritaka; Hisabe, Takashi; Kishi, Masahiro; Takeda, Teruyuki; Yasukawa, Shigeyoshi; Koga, Akihiro; Kinjo, Ken; Hirai, Fumihito; Ueki, Toshiharu; Yao, Kenshi
Abstract: Background: The short‐term efficacy of tacrolimus (Tac) for steroid‐dependent and steroid‐resistant refractory ulcerative colitis (UC) has been demonstrated; however, its long‐term outcomes have not been well documented. Thus, this study aimed to clarify the long‐term outcomes of patients who achieved Tac‐induced remission and identify its predictors. Methods: This study included patients with moderate‐to‐severe active UC who started receiving Tac at our hospital between July 2004 and December 2016. Short‐term treatment response was assessed using the Lichtiger index 3 months after starting Tac, and responding patients were further followed up to assess long‐term outcomes. The primary endpoint was the relapse‐free survival after Tac‐induced remission, and the secondary endpoint was the identification of factors associated with relapse after Tac‐induced remission. Results: The cumulative relapse‐free survival rate at 10 years after Tac‐induced remission was 33.2%. Multivariate analysis revealed that being thiopurine naïve at Tac induction was associated with the absence of relapse (hazard ratio: 0.45; 95% confidence interval: 0.22–0.92). Conclusions: Approximately one‐third of patients who achieved Tac‐induced remission maintained long‐term remission. Being thiopurine naïve at Tac induction was a predictor of the absence of relapse.